Accounting for solicitors - Lawson, Edward (London : Butterworths, 1975)
Accounting for solicitors is aimed at explaining accounting concepts like the basics; adjustments at end of financial year; partnership accounts; manufacturing accounts; non-trading orgnisations; accounting ratios and analysis of accounts; a solicitors books and records.
Includes index.
lje 25/01/2019
Loans
Keywords: Lawyers; Accounting